2018
DOI: 10.1111/febs.14644
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair in trinucleotide repeat ataxias

Abstract: The inherited cerebellar ataxias comprise of a genetic heterogeneous group of disorders. Pathogenic expansions of cytosine-adenine-guanine (CAG) encoding polyglutamine tracts account for the largest proportion of autosomal dominant cerebellar ataxias, while GAA expansion in the first introns of frataxin gene is the commonest cause of autosomal recessive cerebellar ataxias. Currently, there is no available treatment to alter the disease trajectory, with devastating consequences for affected individuals. Inter- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 149 publications
0
14
0
Order By: Relevance
“…The disturbances in DNA reparation in the adult brain are associated with the processes of aging and neurodegeneration. Oxidative metabolism is very important for neuronal functioning, but oxidative stress can cause the single-strand breaks in DNA, leading to alterations in gene expression and even cell death [16]. Cerebellar PCs have been reported to be highly affected by oxidative stress [224].…”
Section: Modifiers Of Transcription Translation and Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The disturbances in DNA reparation in the adult brain are associated with the processes of aging and neurodegeneration. Oxidative metabolism is very important for neuronal functioning, but oxidative stress can cause the single-strand breaks in DNA, leading to alterations in gene expression and even cell death [16]. Cerebellar PCs have been reported to be highly affected by oxidative stress [224].…”
Section: Modifiers Of Transcription Translation and Dna Repairmentioning
confidence: 99%
“…Studies with these model systems revealed the disturbances in the morphology, biochemistry, and neurophysiology of the PCs and the cerebellar circuits [7,8] and helped to identify the possible molecular mechanisms of the disease. Aggregation, oxidative stress, disturbed cell signaling, dysregulation of calcium homeostasis, abnormal autophagy, and impaired DNA processing all seem to be involved in SCA2 molecular pathogenesis [9][10][11][12][13][14][15][16]. The promising data obtained in these studies gave rise to some perspective therapeutic approaches that may give decisive results in the treatment of SCA2 patients.…”
Section: Introductionmentioning
confidence: 98%
“…The review is primarily intended for neurobiologists, physicians and others working in the field, or those interested in the general topic, but who are unfamiliar with DNA repair. For additional analysis, the reader is directed to other recent review articles [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…The authors highlight the role of epigenetics and other genetic factors as modifiers in cerebellar ataxias due to trinucleotide repeat expansions [14]. The authors highlight the role of epigenetics and other genetic factors as modifiers in cerebellar ataxias due to trinucleotide repeat expansions [14].…”
mentioning
confidence: 99%
“…Finally, Wai Yan Yau et al review the importance of DNA repair pathways in modifying inherited cerebellar ataxias. The authors highlight the role of epigenetics and other genetic factors as modifiers in cerebellar ataxias due to trinucleotide repeat expansions [14].…”
mentioning
confidence: 99%